Globalization and Income Inequality: A Panel Data Analysis of 68 Countries - Syed Muhammad Atif; Mudit Srivastav; Moldir Sauytbekova; Udeni Kathri Arachchige (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The causal effect of globalization on income inequality is an issue of significant academic interest. On one hand globalization is considered to promote global economic growth and social progress, while on the other, it is blamed for growing income inequality and environmental degradation, causing social degeneration and difficulty of competition. This paper analyses the impact of globalization on income inequality by estimating static and dynamic models for panel data of 68 developing countries over the period of 1990-2010. The results conform to a priori expectations and it is suggested that an increase in globalization in developing countries leads to an increase in the level of income inequality. However, this analysis suffers from certain limitations, which lead to the conclusion that perhaps a simple, overarching relationship does not exist in the subject matter. Rather it is possible that the impact of globalization on income distribution varies between nations, depending on the structures and institutions that are in place in each country.
Keywords: F63; C33; 330; Globalization; Income Inequality; Panel Data; Globalization; Income distribution